András Hegedüs - the Former Premier under Rákosi Returned to Budapest from Moscow and Received a State Pension - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Die Presse (Vienna) report.